COVID-19 Pandemic and Death Anxiety in Security Forces in Spain - Lázaro-Pérez, Cristina (Int J Environ Res Public Health, 2020)
The pandemic caused by the SARS-CoV-2 coronavirus, which produces COVID-19 disease, has revealed to political and social circles a series of needs that have not yet been met. The workers of the State Security Forces and the Armed Forces have done an extraordinary job to try to alleviate the effects that the pandemic has had on the population and to return stability to the citizenry as much as possible. In this context, the following investigation is developed based on two objectives: (PO1) to know the level of anxiety in the face of death in these professionals; (PO2) to determine the predictive variables in the above-mentioned phenomenon. Professionals from all over Spain have participated in the study (n = 2079). From a quantitative perspective, a questionnaire was developed from the Collet–Lester death anxiety scale. The results show a total level of 69.2% in the scale, as well as some higher levels about the fear of death of others (82.1%) and the fear of the process of dying of others (78.2%). On the other hand, from the binary logistic regressions, four variables are evidenced that condition the risk of suffering death anxiety: (a) certainty of needing psychological treatment in the future; (b) absence of Individual Protection Equipment (PPE); (c) high levels of Emotional Exhaustion; (d) high levels of depersonalization—these last two come from the Maslach and Jackson Burnout scale. These data show a need for training and intervention in the emotional and psychological demands of the professionals of the Armed Forces and State Security Forces, as well as the obligation to develop a continuous dialogue with the institutions they represent to foster the feeling of belonging to them. It is essential, regardless of the serious consequences that the virus has caused, to understand the psychosocial and emotional demands of enforcement agents and to improve their occupational health.